EFEKTIVITAS DAN TINGKAT PARTISIPASI MASYARAKAT TERHADAP PROGRAM PENGENTASAN KEMISKINAN PERKOTAAN (P2KP) DI KOTA BANDAR LAMPUNG - Yanfika, Helvi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
The goal of provision of venture capital through P2KP is to improve the economy and provide infrastructure assistance to the urban poor in the form of concern that the government is